2018
DOI: 10.1111/ijfs.13815
|View full text |Cite
|
Sign up to set email alerts
|

Porous‐structured extruded instant noodles induced by the medium temperature α‐amylase and its effect on selected cooking properties and sensory characteristics

Abstract: Summary To enhance the rehydration and palatability characteristics of extruded noodles, a new type of instant noodles with a well‐developed porous structure was successfully created by cooperating medium temperature α‐amylase (MTA) with extrusion technique. To explain the formation reason of the porous structure, a detailed mechanism analysis was firstly carried out. It turned out that a portion of starch was degraded into water‐soluble dextrin during the enzymatic extrusion treatment. Besides, a slight restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Some efforts have been made to improve the utilization of gluten‐free materials in pasta making through raw material pretreatment, processing technology or technical addition to replace gluten functionality (Bouasla et al, ; Detchewa, Thongngam, Jane, & Naivikul, ; Ferreira et al., ; Fiorda, Soares, da Silva, Souto, & Grosmann, ; Li, Jiao, Deng, Rashed, & Jin, ; Marti, Seetharaman, & Pagani, ; Sarawong, Rodríguez Gutiérrez, et al, ; Sopade, ; Wardy et al, ). The use of additives (hydrocolloids (e.g., gums or carboxyl methyl cellulose) and emulsifiers) has been shown to improve the quality and sensory properties of gluten‐free pasta (Hager, Zannini, & Arendt, ) as well as the nutritional quality of cereal foods (Gao et al, ; Giuberti and Gallo, ).…”
Section: Introductionmentioning
confidence: 99%
“…Some efforts have been made to improve the utilization of gluten‐free materials in pasta making through raw material pretreatment, processing technology or technical addition to replace gluten functionality (Bouasla et al, ; Detchewa, Thongngam, Jane, & Naivikul, ; Ferreira et al., ; Fiorda, Soares, da Silva, Souto, & Grosmann, ; Li, Jiao, Deng, Rashed, & Jin, ; Marti, Seetharaman, & Pagani, ; Sarawong, Rodríguez Gutiérrez, et al, ; Sopade, ; Wardy et al, ). The use of additives (hydrocolloids (e.g., gums or carboxyl methyl cellulose) and emulsifiers) has been shown to improve the quality and sensory properties of gluten‐free pasta (Hager, Zannini, & Arendt, ) as well as the nutritional quality of cereal foods (Gao et al, ; Giuberti and Gallo, ).…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics make semolina flour a superior material for pasta production. However, different types of cereal flours are being utilized for pasta production due to market trends, that demand high nutritional characteristics, together with the development of alternative raw materials for gluten‐free pasta (Li, Jiao, Deng, Rashed, & Jin, ).). Unfortunately, the gluten‐free flours (maize, rice, millet, and sorghum) cannot create a sufficiently strong binding network to produce the required quality of dough (Gao et al, ; Morreale et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, a larger pore size will absorb water constantly and the starch noodle will become swollen, weakening the starch gel structures, which was consistent with the conclusion of the cooking properties. Li et al (2018) also reported that part of the porous structures would be collapsed when excess MD is incorporated in extruded instant wheat noodles [ 41 ].…”
Section: Resultsmentioning
confidence: 99%